'… and I remember every single session!' – on the usefulness of making reflective books as active note-taking. (1st June 2013) - Gröppel-Wegener, Alke; Williamson, Sarah
This mainly visual essay attempts to give a glimpse of the potential reflective book-making has as note-taking through showcasing a variety of the artefacts produced during a number of Writing in Creative Practice workshops. It is interspersed with some of the quotations we use to put this activity into a larger context of making, thinking and reflective practice.